Peran Pemerintah Desa Dalam Mengembangkan Potensi Pariwisata Desa Pasca Covid-19: (Studi Pada Wisata Dusun Tawun Desa Sekotong Barat Kecamatan Sekotong Kabupaten Lombok Barat) - Wahyu Trisno Aji; Lara Aprilia (Jurnal Kabar Masyarakat, 2024)
The village has tried its best to develop village tourism. They are active in looking for investors, holding promotional events, and carrying out innovations such as diving activities to attract visitors. Even though it has not yet reached perfection, the role of village government is considered positive by the community. The response from the local community also highlights the important role of village government in building public facilities, such as roads and other accessibility. This is considered crucial so that tourists can easily access and enjoy the village's tourism potential. In the context of the post-COVID-19 pandemic, the community in Tawun village is also aware of the changes and innovations made by the village government to overcome the impact of the pandemic, such as focusing on tourism, fishing and rebuilding village MSMEs. From the results of this research and discussion, it can be concluded that the role of village government, especially in the context of developing village tourism potential, is very important. The village government in Tawun Hamlet, West Sekotong Village, Sekotong District, West Lombok Regency, has made maximum efforts to overcome the impact of the pandemic, rebuild tourism potential, and involve the community in the development process. Even though there are still several obstacles and challenges, the efforts made by the village government are expected to have a positive impact on the economy and welfare of the local community.